Over 15 years: the advancement of transcatheter mitral valve repair - Denti, Paolo; Sala, Alessandra; Belluschi, Igor; Alfieri, Ottavio (Annals of Cardiothoracic Surgery, 2020)
Patients with severe symptomatic mitral regurgitation, if left untreated, have a poor prognosis. In those patients not eligible for mitral valve (MV) surgery, percutaneous repair may improve clinical outcomes. In the past 15 years several devices have been developed to address different MV lesions. This manuscript will review the advancement of transcatheter MV repair through the years, focusing on technologies for which consistent clinical data is available.